2007
DOI: 10.1111/j.1365-2648.2007.04276.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ career preferences: a Norwegian study

Abstract: Students' career preferences are an important issue to various stakeholders: to university administration, career counselors, higher education policy makers as well as to human resource managers in companies. Students, whose career preferences and goals are fulfilled, are better and more highly motivated employees. By a questionnaire survey carried out in 2016 in two institutions of higher education the present study compares career preferences and attitudes of 478 German and Croatian students. Factor analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
131
3
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(159 citation statements)
references
References 14 publications
12
131
3
13
Order By: Relevance
“…Our findings are consistent with previous research studies [6,8,11,12], and the results were contradicting to findings from a previous study from India [13].…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Our findings are consistent with previous research studies [6,8,11,12], and the results were contradicting to findings from a previous study from India [13].…”
Section: Discussioncontrasting
confidence: 56%
“…The major reason to choose nursing profession was to serve the community 53 (58.2%), followed by better earning 31 (34.1%), parents wish 25 (27.5%), social status 23 (25.3%), and intrinsic interest in perusing nursing profession 17(18.7%). Other studies also found that the main characteristic which influenced career decision remains care and concern for others, desire to help, followed by job security, information and advice from practicing nurses, role of family members, friends, parents, mentors, role models, and influence of ideals in career formulation [1][2][3][4][5][6][7][8][9][10][11]13,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivators did however change from altruistic values such as helping others, to the more extrinsic values of salary and job security. In contrast, a larger study by Kloster et al (2007) found that career preferences changed significantly during the pre-registration programme. In this longitudinal study of 620 student nurses from 5 Norwegian universities, students' preferences changed from midwifery and children's nursing at commencement of the course to medical and surgical nursing in the final year.…”
Section: Literature Reviewmentioning
confidence: 83%
“…I samfunnsdebatten har det i de senere årene blitt diskutert hva som skal til for at sykepleiere skal velge å arbeide innenfor eldreomsorgen (Thorenfeldt 2009 Kloster et al (2007) fant i sin studie at sykepleierstudentene i første del av studiet var mest interessert i å arbeide med barn eller bli jordmor etter endt bachelorutdanning i sykepleie. Dette funnet støttes av funn i en studie av Happel (1999).…”
Section: Artikkelens Hensikt Og Målunclassified